Investor Characteristics and their Impact on the Decision to use a Robo-advisor - Andreas Oehler; Matthias Horn; Stefan Wendt (Journal of Financial Services Research, 2021)
We survey 231 undergraduate students to analyze how retail investors' characteristics influence their decision to use a robo-advisor. Characteristics such as the willingness to take risk, extraversion, and optimism are significant in univariate tests but the willingness to take risk and the internal locus of control are significant in multivariate settings. Participants who use the robo-advisor invest more and are more likely to also invest on their own in both stocks and bonds. We also find statistically significant differences between participants who exclusively use the robo-advisor for investments in stocks and bonds and participants who use the robo-advisor and invest some money in stocks and bonds on their own.
Keywords: D14; G11; G24; G29; 330; Robo-advisor; Financial Advice; Portfolio Management; Investments; Personal Finance; Household Finance